The effect of universal infant vaccination on the prevalence of hepatitis B immunity in adult solid organ transplant candidates. Issue 1 (14th October 2020) - Koc, Özgür M.; Kuypers, Dirk; Dupont, Lieven J; Vos, Robin; Van Keer, Jan M.; Van Cleemput, Johan; Robaeys, Geert; Oude Lashof, Astrid; Kramer, Matthijs; Verleden, Geert; Verbeek, Jef; Nevens, Frederik
Abstract: Background: Hepatitis B virus (HBV) immunity is recommended to optimize outcomes after solid organ transplantation (SOT). This study assessed the prevalence and predictors of HBV immunity at the time patients were placed on transplant waiting list over a period from 1997 to 2019 in a low HBV endemic region. Methods: Data were obtained from the University Hospitals Leuven transplant database. Minors and patients with past/current HBV infection were excluded. From 1986, Belgian patients are covered by the universal infant vaccination; therefore, birth cohort was stratified in those born ≥1986 vs <1986. Results: The study population consisted of 3297 SOT candidates. HBV immunity rate was superior in renal transplant candidates (55.3%), and this number was 21.5%, 15.4% and 16.8% for liver, cardiac and pulmonary transplant candidates, respectively, P < .001. Among liver transplant candidates, HBV immunity rate was 14.8% in decompensated cirrhotic patients and 27.9% in those without advanced cirrhosis ( P < .001). The overall immunity rate increased from 19.3% in period 1997‐2008 to 32.8% in 2009‐2019, P < .001. In multivariable analyses, younger age (odds ratio (OR) 95% confidence interval (CI): 0.97‐0.98, P < .001) and birth cohort ≥ 1986 (OR 95% CI: 1.18‐2.66, P = .006) were associated with increased HBV immunity. Conclusion: An increase in HBV immunity was observed over a 20‐year period related to the introduction of universal infant HBV vaccination. Nevertheless, this study highlights the low overall HBV immunity at the time of listing for organ transplantation and points out the need of an increased awareness and vaccination strategy at an early disease stage.